1983
DOI: 10.1063/1.332294
|View full text |Cite
|
Sign up to set email alerts
|

Spin coated amorphous chalcogenide films: Structural characterization

Abstract: Thin films that are substantially amorphous arsenic sulfide have been prepared by spin deposition from solutions of n-propylamine or n-butylamine. These materials have been investigated by nuclear magnetic resonance, infrared absorption, and elemental analysis. A structural model is suggested based on As2S3 clusters surrounded by amine as an amine salt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 46 publications
3
47
0
Order By: Relevance
“…Dissolution mechanism of the As-S glass in propylamine was reported by Chern and Lauks [19]. Authors proposed a formation of nano-colloidal clusters of glass with nano-meter size, which are solvated by molecules of solvent.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Dissolution mechanism of the As-S glass in propylamine was reported by Chern and Lauks [19]. Authors proposed a formation of nano-colloidal clusters of glass with nano-meter size, which are solvated by molecules of solvent.…”
Section: Resultsmentioning
confidence: 96%
“…Some chalcogenide glasses can be dissolved in highly volatile amines such as propyl-or butylamine forming nano-colloidal solutions [19,20]. Dissolution mechanism of the As-S glass in propylamine was reported by Chern and Lauks [19].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Thin films of chalcogenides have been primarily deposited onto substrates using vacuum coating techniques, particularly by thermal evaporation. Some laboratory studies [7][8][9][10][11] have shown that binary As-S chalcogenides can be coated as amorphous films using spin-coating technique from amine solutions. Spin-coated films have demonstrated similar properties and potential applications [6] as vacuum deposited films but the spin-coating deposition method is technologically easier and cheaper.…”
Section: Introductionmentioning
confidence: 99%
“…As 2 S 3 was first considered as a material for photography and then as a potential photoresist, with methods for spin coating it and studies of the properties of spun films appearing in the early 1980s [6][7][8]. Studies of the dependence of the optical properties of spin-coated As 2 S 3 films on illumination soon followed [9,10].…”
Section: Introductionmentioning
confidence: 99%